The Influence of Independence, Competence, Auditor Experience, and Due Professional Care on Audit Quality : An Empirical Study at Public Accounting Firms in Surabaya - Gilbert Alexander H. Sipahelut; Tri Ratnawati (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the influence of independence, competence, auditor experience, and due professional care on audit quality. The research focuses on auditors in Public Accounting Firms (PAFs) operating in the Surabaya region. A quantitative approach was employed, with data collected through questionnaires distributed to 100 auditors from 23 PAFs in Surabaya. The data were analyzed using Partial Least Squares (PLS) with the assistance of SmartPLS 4 software. The results indicate that auditor competence has a positive and significant effect on audit quality, while independence, auditor experience, and due professional care do not show significant influences. These findings suggest that PAFs should prioritize enhancing auditor competence to improve audit quality.